2014
DOI: 10.1136/bjophthalmol-2014-305098
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and genotype analysis in patients with macular corneal dystrophy

Abstract: Genetic mutation heterogeneity was revealed. No phenotype heterogeneity was revealed among patients with in vivo corneal morphology assessment or histological analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…Regarding CD corneal morphology analysis, our current SS OCT study complements previous findings demonstrated based on TD, SD, and SS OCT [ 19 23 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Regarding CD corneal morphology analysis, our current SS OCT study complements previous findings demonstrated based on TD, SD, and SS OCT [ 19 23 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 84%
“…TBCD, LCD, and FECD caused increased aCCT and mCCT measured with both devices compared to the control group. MCD was characterized by significant corneal thinning, indicated by previous studies [ 23 , 33 ]. The increase in CCT is the main feature of moderate and advanced FECD, but it is possible that association with other anterior eye segment parameters change is rarely examined.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…[ 1 ] Mutations in corneal carbohydrate sulfotransferase 6 ( CHST6 ) gene are responsible for macular corneal dystrophy (MCD). [ 2 ] The clinical manifestations vary significantly, depending on the anatomical location, and the pattern and severity of the protein deposition. LCD characterized by a network of multiple branching refractive lines or fusiform corneal opacities due to amyloid deposition in the anterior and deep-stromal levels.…”
Section: Introductionmentioning
confidence: 99%